Environmental stimulation improves performance in the ox-maze task and recovers Na+, K+-ATPase activity in the hippocampus of hypoxic–ischemic rats. (16th April 2015) - Rojas, J.J.; Deniz, B.F.; Schuch, C.P.; Carletti, J.V.; Deckmann, I.; Diaz, R.; Matté, C.; dos Santos, T.M.; Wyse, A.T.; Netto, C.A.; Pereira, L.O.
Highlights: Neonatal hypoxia–ischemia caused impairment on ox-maze task. Environmental enrichment reversed functional impairment and Na +, K + -ATPase inhibition. Ox-maze task seems to be a sensitive task to detect cognitive deficits caused by neonatal hypoxia-ischemia. Abstract: In animal models, environmental enrichment (EE) has been found to be an efficient treatment for alleviating the consequences of neonatal hypoxia-ischemia (HI). However the potential for this therapeutic strategy and the mechanisms involved are not yet clear. The aim of present study is to investigate behavioral performance in the ox-maze test and Na +, K + -ATPase, catalase (CAT) and glutathione peroxidase (GPx) activities in the hippocampus of rats that suffered neonatal HI and were stimulated in an enriched environment. Seven-day-old rats were submitted to the HI procedure and divided into four groups: control maintained in standard environment (CTSE), control submitted to EE (CTEE), HI in standard environment (HISE) and HI in EE (HIEE). Animals were stimulated with EE for 9 weeks (1 h/day for 6 days/week) and then behavioral and biochemical parameters were evaluated. Present results indicate learning and memory in the ox-maze task were impaired in HI rats and this effect was recovered after EE. Hypoxic–ischemic event did not alter the Na +, K + -ATPase activity in the right hippocampus (ipsilateral to arterial occlusion). However, on the contralateral hemisphere, HI caused a decrease in this enzyme activity that was recovered by EE. The activities of GPx and CAT were not changed by HI in any group evaluated. In conclusion, EE was effective in recovering learning and memory impairment in the ox-maze task and Na +, K + -ATPase activity in the hippocampus caused by HI. The present data provide further support for the therapeutic potential of environmental stimulation after neonatal HI in rats.